2018
DOI: 10.3389/fpsyg.2018.00340
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Home Numeracy Activities Is Differentially Related to Basic Number Processing and Calculation Skills in Kindergartners

Abstract: Home numeracy has been shown to play an important role in children’s mathematical performance. However, findings are inconsistent as to which home numeracy activities are related to which mathematical skills. The present study disentangled between various mathematical abilities that were previously masked by the use of composite scores of mathematical achievement. Our aim was to shed light on the specific associations between home numeracy and various mathematical abilities. The relationships between kindergar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 71 publications
4
62
2
Order By: Relevance
“…In terms of formal activities, Thompson, Napoli, and Purpura (2017) found that home activities that are explicitly centered on math, such as counting objects, printing numbers, or using number activity books, predicted the early numeracy skills of preschoolers. Similarly, others have found that the frequency of formal numeracy activities predicted children's enumeration skills (Mutaf Yıldız, Sasanguie, De Smedt, & Reynvoet, 2018) and arithmetic skills (Vasilyeva, Laski, Veraksa, Weber, & Bukhalenkova, 2018). Operational numeracy activities predicted symbolic number knowledge for prekindergarten (Susperreguy et al, 2018) and kindergarten children (Skwarchuk et al, 2014).…”
Section: Numeracy Activitiesmentioning
confidence: 77%
See 2 more Smart Citations
“…In terms of formal activities, Thompson, Napoli, and Purpura (2017) found that home activities that are explicitly centered on math, such as counting objects, printing numbers, or using number activity books, predicted the early numeracy skills of preschoolers. Similarly, others have found that the frequency of formal numeracy activities predicted children's enumeration skills (Mutaf Yıldız, Sasanguie, De Smedt, & Reynvoet, 2018) and arithmetic skills (Vasilyeva, Laski, Veraksa, Weber, & Bukhalenkova, 2018). Operational numeracy activities predicted symbolic number knowledge for prekindergarten (Susperreguy et al, 2018) and kindergarten children (Skwarchuk et al, 2014).…”
Section: Numeracy Activitiesmentioning
confidence: 77%
“…Informal activities (i.e., parents' knowledge of number-related games) also had direct effects on nonsymbolic comparison and arithmetic fluency at the end of kindergarten. Prior studies of home numeracy activities and children's performance found that informal and formal activities were differentially related to children's specific numeracy outcomes (Mutaf Yıldız et al, 2018;Skwarchuk et al, 2014). For example, Skwarchuk et al (2014) found that informal activities at age 4 were related to children's nonsymbolic arithmetic skills at age 5, whereas formal activities at age 4 were related to children's knowledge of written digits at age 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we did not assess the role of home numeracy environment in our study. Previous studies have found that home numeracy environment is an important predictor of children’s mathematics achievement (e.g., Manolitsis et al, 2013 ; Deng et al, 2015 ), and the mathematics activities at home may also promote children’s non-symbolic and symbolic estimation (e.g., Mutaf-Yildiz et al, 2018 ). Future studies should examine the effects of home numeracy environment on ANS acuity and mathematics skills.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies on the ecological and cross-cultural validity of the instrument, complemented with qualitative methodologies such as in-depth interviews or observations (e.g., Susperreguy & Davis-Kean, 2016), are an important building block for addressing a timely topic within early mathematics education, namely the contribution of home numeracy activities and specific mathematical competencies (such as basic number processing and calculation skills). By focusing on specific mathematical abilities instead of a general score of mathematics achievement, studies can give an explanation for the contradictory findings in the literature on the association between children's home numeracy and mathematical abilities (Mutaf, Sasanguie, De Smedt, & Reynvoet, 2018). Moreover, future research should include control variables that have been shown to play a role in the relation between home numeracy and mathematics achievement, such as children's age (see for example .…”
Section: Resultsmentioning
confidence: 99%